Ghana : Poverty Reduction Strategy Paper-Volume II. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This volume discusses the Poverty Reduction Strategy (GPRS I) and the Growth and Poverty Reduction Strategy (GPRS II) that addressed the critical poverty issues in Ghana. GPRS I is a comprehensive policy document prepared as a precondition for Ghana under the Highly Indebted Poor Country (HIPC) Initiative. The main component-human development-targets improvement for Ghana's population to access basic needs and essential services. A general assessment shows that Ghana has a positive and significantly stabilized macroeconomic environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet